Análisis de los riesgos laborales y mejoras en el proceso de instalaciones de internet de la empresa Telconet - Zumba Carrera, Esteban Rafael (2016)
The project is comprised of five chapters in which it is on the main aspects of the organization such as: Location, chart, line of business of the organization, mission and vision of the company, the terms associated with security are defined and occupational health the same as serve as a key for identification, risk assessment at work guide, to check how is the current process of internet facilities in the operational area, hazards and risks in the process are identified, additionally performed indicators raised accidents, lost days, and current costs for accidents. Based on the problems identified methodologies that help identify hazards and risks in the process, at the same time control or mitigation measures to control risks in the proposed work it is proposed. Where the radical change in control will be demonstrated accidents and losses caused by accidents. Finally conclusions and recommendations of the results of the practical and theoretical knowledge provided to crews operating with feedback based on results and to express the recommendations of the proposal will be defined.